I mostri della ragione: lo stalinismo - Ventura, Andrea (Il sogno della farfalla, 2008)
The work stems from an analysis of some aspects of Descartes and Spinoza’s philosophy demonstrating, in particular, to what extent the birth of modern rationalism is connected to the development of themes of a religious character. Furthermore, referring back to two previous works published by the author in this very magazine, there is a discussion on the theory of the social contract and the process of alienation of the citizen within the state with reference to Spinoza, Hobbes and Rousseau highlighting among other things how Marx undertook an opposite path without succeeding in identifying and going beyond that combination of reason and religion which feeds the process of alienation. The conclusive part the article offers us some crucial moments of the Soviet experience from the period 1917-41. This reconstruction demonstrates how Marxism, far from having created an opposition to capitalism, has contributed to its creation; this paradoxical result can be attributed in certain aspects to the structural limits of Marxian theory and more specifically to the absence of criticism of the interconnection between reason and religion which is constitutive of modern thinking.